The Study of Life Style and Demographic Characteristics of Iranian Elderly - Taheri, Morteza (Journal of Sports Research, 2015)
Successful aging is largely determined by individual lifestyle choices. The purpose of this study was to determine the Status of Lifestyle in elderly population of Qazvin city. A cross-sectional study was conducted to determine the life style among 183 elderly selected randomly in health clinic. Lifestyle elderly questionnaire in five domains including lifestyle, prevention, exercise, nutrition, stress and relationships was used. Pearson, ANOVA and independent T-tests were applied at significance level of 0.05. The results suggested that life style has a positive correlation with prevention, exercise, nutrition, relationship On the other hand, there was a negative significant correlation between stress and life style, prevention, exercise and the positive relationship were found between exercise and relationships, nutrition. Due to growing elderly population and the importance of healthy lifestyle, it's recommended that appropriate strategies be implemented for improving healthy lifestyle in elderly population. Consequently, Older adults adopting more healthy lifestyles are more likely to maintain active life style.